Dampak Penerapan ODOO ERP Terhadap Kinerja Supply Chain Management Pada PT Anugrah Jaya Group - Femas Galang Samudra Amsa; Yani Prihati; Ana Wahyuni (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
Companies in the digital era need to integrate business processes to improve efficiency and competitiveness. Odoo is an open-source Enterprise Resource Planning (ERP) platform that provides integrated solutions for managing diverse operational functions, including Supply Chain Management (SCM). The implementation of Odoo ERP at PT Anugrah Jaya Group, a company engaged in the sale of gadget accessories, has proven to enhance inventory management efficiency, accelerate order processing, and improve reporting accuracy. The system also reduces the risk of supply delays and strengthens coordination among departments within the supply chain. This system design utilizes Unified Modeling Language (UML) to visualize business process flows and ensure optimal integration. Therefore, Odoo ERP contributes positively to improving SCM performance and serves as a strategy that supports the sustainability of business processes at PT Anugrah Jaya Group.